International experience of linking between research, education and innovation in research and development organizations - Hai, Ha Cong (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Meeting new requirements, research and development (R&D) organizations in countries worldwide had made every effort to find out solutions and take appropriate actions to promote the internal linkage among research, training and innovation in their organizations. Since this was by nature, an internal arrangement, the establishment and maintenance of such a linkage had a number of fundamental advantages relating to management; setting development goals; formulating regimes and policies for the use of human and physical resources; building the confidence in internal workforce. This article introduced some experiences in promoting the link of research, training and innovation by three major R&D organizations in the world, i.e Max Planck Institute and Fraunhofer Institute (Germany), Institut Pasteur (France). On that basis, it provided with some recommendations for Vietnam in promoting the linkage among research, training and innovation in public R&D organizations. Code: 16060301<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">